ANALISIS KEBIJAKAN DALAM MENGATASI KEKURANGAN BIDAN DESA DI KABUPATEN NATUNA - Imam Syafari Dwi Handono Sulistyo Kristiani (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background: Geographical condition of Natuna Islands whichis not in accordance with health development affects thequantity and availability of midwives distributed in villages inthe District of Natuna. In fact, the ratio between the number ofvillages and the number of midwives in the district has not metthe standard proposed by the Ministry of Health. Unfortunately,there are still around 13 villages from 51 villages that have nomidwives serving in those villages. The location of 13 villagesare separate Island, and it caused lack of provide access toquality health care services. One of efforts done by the localgovernment is to attract midwives’ interest through a varietyof strategies and policies in several fields such as financing,incentive, regulation, organization, and stakeholders’ behaviors.Method: This was a descriptive study with study-case designby using qualitative method. Study case in this study was asingle holistic study case. The informants were head of healthoffice, head of health empowerment and promotion division,head of general affairs and employment sub division, head ofBKD, head of Local Development Planning Agency, theCommission Two of Local Legislative, heads of communityhealth centers, and village midwives. The study case designaimed to know policies in overcoming the lack of midwives inthe District of Natuna.Results: The local government financing policy allocated thebudget or health less than 15%, which was only 3-4% usedfor improving the health workers’ capacity. The incentive givingfor midwives was relatively small compared to the incentiveregulated by the Ministry of Health. There was no specificregulation from the local government, so that the policy wasconsidered not optimal. In the organizational level, the role ofstakeholders was in accordance with their duty and provision;however, the f inal decision was dependent upon LocalLegislative and the local government’s leader. Lastly, midwives’low interest to work in Natuna was caused by its geographicalcondition.Conclusion: Local government’s policy in the field of financing,incentive, organization, regulation, and behavior in overcomingthe lack of village midwives was considered not optimalbecause of the absence of specific policy from the localgovernment in this matter. In addition, midwives’ low interest towork in Natuna contributed the lack of midwives in this district.Keywords: policy analysis, the lack of village midwives